EVALUASI IMPLEMENTASI PROGRAM SASARAN KESELAMATAN PASIEN DI RSUD BREBES JAWA TENGAH TAHUN 2021 - Aulia, Alda Dwi Rizki; Hastuti, Siti Kurnia Widi (Prosiding Seminar Kesehatan Nasional Sexophone, 2024)
Patient safety is the main reference in carrying out a health service process in hospitals and health centers. One effort to reduce/minimize and prevent incidents in patients is by implementing a patient safety system. Patient safety goals (SKP) are efforts to prevent patient safety incidents in hospitals. Therefore, this research evaluates how the SKP program at RSUD Brebes, Central Java is implemented. This research uses a qualitative descriptive method with a phenomenology approach. This research was carried out with the CIPP Evaluation concept. Informants were determined using a purposive sampling technique. The research informants consisted of 5 people, namely the Head of Nursing at Brebes Regional Hospital, Member Representatives from KMKP, the Head of Pharmacy, the Head of the Nursing Room, Installation Section. The instruments in the research are an interview guide, observation form (checklist), and recording equipment. The implementation of Patient Safety Goals at RSUD Brebes has been optimal, both from the SKP Implementation Objectives, Policies, and Guidelines, the need for SKP implementation as well as the Facilities and Facilities at the Hospital, HR, SKP Activities/Implementation, and the 6 SKP Implementation Process at the Brebes Hospital. The error that often occurs is that the compliance and habits of officers towards the implementation of SPO/SKP Implementation Guidelines have not been fully implemented. Implementation of Patient Safety Goals at the RSUD Brebes has been going well, health workers at the hospital have received socialization from the Hospital on the Implementation of Patient Safety Goals referring to the Minister of Health Regulation and KARS. In its implementation, it is quite good and runs by the policies of the hospital, starting from the Target of Accuracy of Patient Identification to the Target of Reducing the Risk of Accidents Due to Fall.